Evaluasi Kemajuan Proyek Preservasi Jalan Batas Provinsi Riau – Merlung – Batas Kabupaten Tanjung Jabung Barat dengan Metode Nilai Hasil - Imam Haji Batubara; Ade Nurdin; Dyah kumalasari (Universitas Muara Bungo, 2021)
Population increase is increasing from time to time. As the population increases, the need for basic goods and logistics also increases. Smoothness to meet needs depends on adequate infrastructure, one of which is roads. Road is an infrastructure that connects one area to another. Damage to roads can break the wheels of the economy in an area and slow down the arrival of basic goods for the needs of the population in an area. One of the activities that can improve this is road repairs. The central government through the Ministry of Public Works and Public Housing runs a program called Longsegment Road Preservation which aims to obtain stable and uniform road conditions in one longsegment. Longsegment Road Preservation is one solution to repair damaged roads, but it is possible that activities in the field do not go according to plan, so it is necessary to evaluate the progress of a work. One of the Longsegment Road Preservation projects in Jambi Province is the Road Preservation of the Riau Province Boundary – Merlung – West Tanjung Jabung Regency. In order to see whether this work is good or not, an evaluation of the project's progress is carried out using the Result Value method. The results of this study indicate that the time and cost performance of the Road Preservation of the Riau Province Boundary – Merlung – West Tanjung Jabung Regency shows poor performance based on the CV = Rp. -3,037,850.00, CPI = 0.999 1,000, SV = Rp. -428,871,785.62, SPI = 0.935 1,000. The realization of the Road Preservation of the Riau Province Boundary – Merlung – West Tanjung Jabung Regency implementation was not in accordance with the plan, this was based on weekly reports in the twelfth week of realization progress of 25.680% while the planned progress was 28.554% so that there was a deviation of -2.875%